2022
DOI: 10.1002/ejoc.202200417
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Applications of Photocatalyzed Halogen‐Radical Mediated Hydrogen Atom Transfer for C−H Bond Functionalization

Abstract: The opportunity to activate C(sp3)−H bonds via homolytic cleavage by means of halogen radicals has long been disregarded in synthetic endeavors due to the unpredictable selectivity. Nowadays, photocatalysis has established itself as a method of choice for the generation of such reactive intermediates under mild conditions. This Minireview collects recent examples showcasing how photocatalytic manifolds have been used to tame aggressive halogen radicals to activate C(sp3)−H bonds via Hydrogen Atom Transfer (HAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 131 publications
0
54
0
Order By: Relevance
“…6g , 27 , 28 In this scenario, the employed photocatalyst would oxidize the bromide generated upon oxidative addition to afford the halogen atom. 29 In fact, we found that the luminescence of the photocatalyst was quenched by TBABr and silane with comparable rates ( k SV = 325 and 121 M –1 , respectively). However, since the concentration of the latter is much higher, a direct photocatalyzed HAT is more likely.…”
Section: Resultsmentioning
confidence: 75%
“…6g , 27 , 28 In this scenario, the employed photocatalyst would oxidize the bromide generated upon oxidative addition to afford the halogen atom. 29 In fact, we found that the luminescence of the photocatalyst was quenched by TBABr and silane with comparable rates ( k SV = 325 and 121 M –1 , respectively). However, since the concentration of the latter is much higher, a direct photocatalyzed HAT is more likely.…”
Section: Resultsmentioning
confidence: 75%
“…The sheer complexity of biologically active molecules demands continuous efforts from synthetic organic chemists to develop new and more efficient synthetic strategies . In addition, spurred by the principles of green chemistry and engineering, there is also a growing desire to develop greener and more sustainable processes. With these boundary conditions in mind, it is only natural that photocatalysis has received significant attention from researchers in both academia and industry, providing benefits that include high selectivity, mild reaction conditions, improved safety, and the use of photons as green and traceless reagents. …”
Section: Introductionmentioning
confidence: 99%
“…The possibility to exploit photonic energy in organic synthetic endeavors has dramatically impacted the way chemists assemble molecules. In particular, photocatalysis has enabled a convenient entry to open-shell intermediates, 1 spurring the development of efficient manifolds for the generation of C-, 2 N-3 and O-4 centered radicals, as well as halogen radicals, 5 which can be subsequently used to forge new chemical bonds. 6 In contrast, boron-based congeners have long remained in obscurity, 7 mainly due to the intrinsic difficulties associated with the handling of these highly electron-deficient and unstable intermediates.…”
Section: Introductionmentioning
confidence: 99%